2006
DOI: 10.2353/ajpath.2006.050575
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Psychological Stress in Rats Induces Intestinal Sensitization to Luminal Antigens

Abstract: There is increasing evidence that stress plays a role in the pathophysiology of chronic intestinal disorders, but the mechanisms remain unclear. Previous studies in rats have revealed that stress decreases gut barrier function and allows excessive uptake of luminal material. Here, we investigated whether chronic psychological stress acts to induce sensitization of intestinal tissues to oral antigens. Rats were subjected to 1 hour per day of water avoidance stress or sham stress daily for 10 days, and horseradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
139
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 139 publications
(151 citation statements)
references
References 50 publications
(55 reference statements)
10
139
1
1
Order By: Relevance
“…1 In an elegant series of experiments presented in this issue of The American Journal of Pathology, Yang and colleagues demonstrate that, in a genetically susceptible host, stress contributes to the development of food allergies by increasing transepithelial permeability in a corticotropinreleasing hormone (CRH)-dependent fashion. 5 Their report offers convincing data to support their earlier groundbreaking observations that stress may alter epithelial function. Using a model of water-avoidance-stress in rats, the authors observed that during chronic stress intestinal antigen uptake is increased, which in turn sensitizes the host to mast cell-induced enteropathy on secondary exposure to the same antigen.…”
supporting
confidence: 73%
“…1 In an elegant series of experiments presented in this issue of The American Journal of Pathology, Yang and colleagues demonstrate that, in a genetically susceptible host, stress contributes to the development of food allergies by increasing transepithelial permeability in a corticotropinreleasing hormone (CRH)-dependent fashion. 5 Their report offers convincing data to support their earlier groundbreaking observations that stress may alter epithelial function. Using a model of water-avoidance-stress in rats, the authors observed that during chronic stress intestinal antigen uptake is increased, which in turn sensitizes the host to mast cell-induced enteropathy on secondary exposure to the same antigen.…”
supporting
confidence: 73%
“…HRP flux was performed with established procedures that were published elsewhere. 13 In separate experiments, FITC-dextran (10 mg/ml; 1, MW54000; 2, MW570 000) was added to the (e) HRP flux was performed with the T84 monolayers at time points as denoted on the X axis of the bar graphs. Each Transwell was only used for one permeability experiment.…”
Section: Cell Culturementioning
confidence: 99%
“…Some studies in mice models proved that physical and psychological stress can induce intestinal sensitisation to luminal antigens and oral tolerance disruption by inducing alterations in colonocyte differentiation and decreased expression of RNAm encoding tight junction proteins, with a consequent increase in paracellular permeability and excessive uptake of luminal material. 8,9 Stress is also associated to gut flora changes, with the possible consequences already discussed above.…”
Section: To the Editormentioning
confidence: 99%